Rapid and simple identification of Beijing genotype strain of Mycobacterium tuberculosis using a loop‐mediated isothermal amplification assay. (July 2016) - Nagai, Yuhki; Iwade, Yoshito; Nakano, Manabu; Akachi, Shigehiro; Kobayashi, Takashi; Nishinaka, Takamichi
ABSTRACT: Beijing genotype strains of Mycobacterium tuberculosis are geographically widespread and pose a notorious public health problem, these strains causing outbreaks of multidrug‐resistant tuberculosis (TB); some studies have reported an association with drug resistance. Because the prevalence of Beijing strain has a substantial impact on TB control programs, the availability of a rapid and reliable method for detecting these strains is important for epidemiological monitoring of their circulation. The main methods currently used to identify Beijing genotype strains are IS 6110 DNA fingerprinting, spoligotyping and PCR to detect specific deletions such as region of difference (RD)207. More recently, multiplex PCR assay using a Beijing‐specific single nucleotide polymorphism (SNP) has been developed for detecting Beijing lineage strains. However, these methods are time‐consuming and technically demanding. In the present study, a loop‐mediated isothermal amplification (LAMP) assay that allows specific identification of Beijing genotype strain was developed. This Beijing genotype strain‐identifying LAMP assay was performed 214 clinical isolates and the results compared with those of conventional PCR that targeted RD207 and Rv0679c ‐targreting multiplex PCR for Beijing lineage identification. LAMP assay showed 100% sensitivity and specificity compared with RD207‐PCR. Furthermore, the sensitivity and specificity were 99.3% and 100%, respectively, compared with Rv0679c‐ multiplex PCR. This LAMP assay could be used routinely in local laboratories to monitor the prevalence of the Beijing genotype strain and thereby used to help control the spread of these potentially highly virulent and drug resistant strains.